2013
DOI: 10.1242/jeb.089177
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical output in jumps of marmosets (Callithrix jacchus)

Abstract: In this study we determined the mechanical output of common marmosets (Callithrix jacchus) during jumping. Vertical ground reaction forces were measured in 18 animals while they jumped from an instrumented crossbar to a crossbar located 70 cm higher. From the vertical force time histories, we calculated the rate of change of mechanical energy of the centre of mass (dE/dt). The mean value of dE/dt during the push-off amounted to 51.8±6.2 W kg −1 body mass, and the peak value to 116.4±17.6 W kg −1 body mass. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 24 publications
2
8
0
Order By: Relevance
“…P FMS,peak of different species needs to be compared within the same experimental set-up using the same solutions in order to make definitive statements about possible differences in power-generating capacity. In this context it is interesting to note, as we did before (Bobbert et al, 2014), that the reported P MMS,mean delivered by marmosets and bushbabies during a vertical jump is similar to or even higher than P MMS,peak measured for supramaximally stimulated in situ rat m. gastrocnemius medialis (i.e. 530 W kg −1 muscle mass) at 35°C (Furrer et al, 2013).…”
Section: Marmosets Have Fast Muscles and A Unique Expression Of Type supporting
confidence: 66%
See 4 more Smart Citations
“…P FMS,peak of different species needs to be compared within the same experimental set-up using the same solutions in order to make definitive statements about possible differences in power-generating capacity. In this context it is interesting to note, as we did before (Bobbert et al, 2014), that the reported P MMS,mean delivered by marmosets and bushbabies during a vertical jump is similar to or even higher than P MMS,peak measured for supramaximally stimulated in situ rat m. gastrocnemius medialis (i.e. 530 W kg −1 muscle mass) at 35°C (Furrer et al, 2013).…”
Section: Marmosets Have Fast Muscles and A Unique Expression Of Type supporting
confidence: 66%
“…For instance, for the Muscle mass-specific peak power (P MMS,peak ) was derived from the whole-muscle F-V relationship, which was estimated by adding at each velocity the force output of the relative fractions of different fibre types. (A,B) F-V (dashed) and P-V (solid) curve of marmoset (thick) and human (thin) VL (A) and GM (B Bobbert et al, 2014). These values are 6.3-fold and 3.7-fold those reported for humans, respectively, and 3.3-and 1.6-fold those shown here for the marmoset.…”
Section: Marmosets Have Fast Muscles and A Unique Expression Of Type supporting
confidence: 52%
See 3 more Smart Citations